PERANCANGAN SISTEM PENCATATAN STOK ROKOK REAL-TIME BERBASIS WEB MENGGUNAKAN METODE V-MODEL - Abdillah, Muhammad; Elhanafi, Andi Marwan (PROGRESS, 2025)
The rapid development of information technology has encouraged companies to shift from manual processes to digital-based systems in order to improve operational efficiency and data accuracy. In cigarette distribution companies, manual recording of stock and distribution activities often causes various problems such as delayed reporting, discrepancies between warehouse and store stock data, and difficulties in generating accurate and timely reports. Based on a case study in a cigarette distribution company, a Web-Based Cigarette Distribution and Stock Management System was developed as a digital solution. The system was designed using the V-Model methodology, which emphasizes a strong correlation between development stages and testing phases. The system’s main features include stock data management (CRUD), stock request submission by sales, request verification by admins, as well as monitoring and report generation by managers. The implementation utilized PHP & MySQL for the backend, Bootstrap for the user interface, and AJAX to enable real-time data updates. System testing using the Black Box Testing method demonstrated that all key functionalities operated according to user requirements. The system successfully improved distribution efficiency, ensured data accuracy through input validation, and provided centralized data management for easier monitoring and auditing. Consequently, this system enables faster, more transparent, and integrated cigarette distribution processes, thereby supporting the company’s work effectiveness and managerial decision-making.